HBx acts as an oncogene and promotes the invasion and metastasis of hepatocellular carcinoma both in vivo and vitro. Issue 3 (March 2021) - Yang, Shizhong; Liu, Yanfeng; Feng, Xiaobin; Wang, Xiaojuan; Wu, Meilong; Gong, Lei; Shu, Bin; lu, Qian; Dong, Jiahong
Abstract: Background and Aims: Hepatitis B virus X (HBx) has been reported to be closely related to hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). This study aimed to detect the expression pattern of HBx and explore whether HBx protein can promote HCC invasion and metastasis both in vivo and vitro. Methods: HBx expression was detected in HCC tissues via immunochemistry. A recombinant adenovirus vector containing the HBx gene was constructed and transfected into the HCC cell line SMMC-7721. Wound healing, transwell migration, and invasion assays were performed to evaluate migration and invasion potentials. A splenic implant tumor nude mice model was established to confirm its invasion and metastatic abilities in vivo. Results: The positive rate of HBx in HCC tissues was 67.89%. HBx overexpression significantly promoted the migration and invasion abilities of SMMC-7721 cells in vitro. The tumor model showed that splenic implant tumor volume and number of liver metastatic tumor nodes were significantly larger and higher in the HBx overexpression group than in the control group. Conclusions: HBx is highly expressed in HCC tissues and promotes HCC invasion and metastasis both in vivo and vitro with oncogene activity, thereby suggesting that HBx can serve as a novel therapeutic target in HCC.